2010
DOI: 10.1029/2009gl041683
|View full text |Cite
|
Sign up to set email alerts
|

Radical‐initiated formation of organosulfates and surfactants in atmospheric aerosols

Abstract: Many atmospheric aerosols contain both organic compounds and inorganic material, such as sulfate salts. In this work, we show that these sulfates could trigger some chemical transformations of the organic compounds by producing sulfate radicals, SO4−, when exposed to UV light (280–320 nm). In particular, we show by mass spectrometry (LC/ESI‐MSMS) that isoprene, methyl vinyl ketone, methacrolein, and α‐pinene in irradiated sulfate solutions (ammonium and sodium sulfate) produce the same organosulfates as previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
225
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(245 citation statements)
references
References 39 publications
(70 reference statements)
16
225
0
Order By: Relevance
“…In the Amazon, Kourtchev et al (2016) previously found a similar subset of these unidentified CHOS compounds in SOA samples, suggesting a biogenic influence. Many organosulfates and nitrooxy-organosulfates, previously reported in laboratory studies, ambient aerosols, and cloud water as derived from monoterpene oxidation (Boone et al, 2015;Hamilton et al, 2013;Iinuma et al, 2007aIinuma et al, , b, 2009Kristensen et al, 2016;Kristensen and Glasius, 2011;Lin et al, 2012;Mazzoleni et al, 2012;Nguyen et al, 2012b;Nozière et al, 2010;O'Brien et al, 2014;Pratt et al, 2013;Stone et al, 2012;Surratt et al, 2008), were detected in the biogenic-influenced cloud water samples (Table 2), also consistent with monoterpene emissions along the air mass trajectories (Guenther et al, 2006). In this study, the required solid-phase extraction step precluded the detection of isoprene-derived organosulfates, which would have been removed prior to analysis.…”
Section: Biogenic Influencesupporting
confidence: 66%
See 1 more Smart Citation
“…In the Amazon, Kourtchev et al (2016) previously found a similar subset of these unidentified CHOS compounds in SOA samples, suggesting a biogenic influence. Many organosulfates and nitrooxy-organosulfates, previously reported in laboratory studies, ambient aerosols, and cloud water as derived from monoterpene oxidation (Boone et al, 2015;Hamilton et al, 2013;Iinuma et al, 2007aIinuma et al, , b, 2009Kristensen et al, 2016;Kristensen and Glasius, 2011;Lin et al, 2012;Mazzoleni et al, 2012;Nguyen et al, 2012b;Nozière et al, 2010;O'Brien et al, 2014;Pratt et al, 2013;Stone et al, 2012;Surratt et al, 2008), were detected in the biogenic-influenced cloud water samples (Table 2), also consistent with monoterpene emissions along the air mass trajectories (Guenther et al, 2006). In this study, the required solid-phase extraction step precluded the detection of isoprene-derived organosulfates, which would have been removed prior to analysis.…”
Section: Biogenic Influencesupporting
confidence: 66%
“…Organosulfates are suggested to be formed from acidcatalyzed reactive uptake of epoxides onto sulfate aerosol (Surratt et al, 2010), as well as in-cloud radical-radical reactions involving sulfate radicals (Nozière et al, 2010;Perri et al, 2010;Schindelka et al, 2013). Isoprene-and monoterpene-derived organosulfates have been observed in cloud water over the southeastern US (Boone et al, 2015;Pratt et al, 2013).…”
mentioning
confidence: 99%
“…Seven different chemically distinct compounds based on the isoprene carbon backbone, containing epoxy, alcohol, nitrate, and/or sulfate functional groups, have now been identified in ambient SOA Claeys et al, 2004;Wang et al, 2005;Surratt et al, 2007;Altieri et al, 2009;Gómez-González et al, 2008;Surratt et al, 2008;Froyd et al, 2010). Some of these compounds are undoubtedly formed from gas phase processing (Perring et al, 2009a, b;Lockwood et al, 2010;Ng et al, 2008), of isoprene, while other compounds (such as organosulfates) clearly indicate that additional chemical processing is occurring on ambient SOA particles themselves (Cole-Filipiak et al, 2010;Paulot et al, 2009;Surratt et al, 2010;Chan et al, 2010;Minerath et al, 2008Eddingsaas et al, 2010;Szmigielski et al, 2010;Nozière et al, 2010;Rudzinski et al, 2009) We recently investigated some of the potential SOA-phase chemistry for isoprene-related compounds, and proposed an overall mechanism (shown in Fig. 1) that can rationalize the existence of five of the seven observed isoprene-derived SOA components (Darer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[32,33] Organic nitrogen and sulfur compounds have been observed to form in highly concentrated aqueous solutions relevant to wet aerosols. [6,[34][35][36][37] Evidence for the photochemical formation of organosulfates from GLY and other aldehydes is provided through studies of bulk sulfate solutions and through smog chamber experiments with ammonium sulfate seed particles and UV irradiation. [6,35,36] Aerosol mimic solutions containing GLY and inorganic ammonium salts have yielded products with carbon-nitrogen bonds in the absence of major atmospheric oxidants (i.e.…”
Section: Introductionmentioning
confidence: 99%